Provision of COVID‐19 Convalescent Plasma in a Resource‐Constrained State. Issue 12 (8th October 2020) - Ipe, Tina S.; Le, Tuan; Quinn, Brian; Kellar, Stan; Clark, Melisa; Carlisle, Suzanna; Rassmann, Anja; Hennigan, Steve; Ridenour, Terry; Roberts, Anthony; Avery, David; Ryan, Stefanie; et al.
Abstract: Background: Arkansas is a rural state of 3 million people. It is ranked fifth for poverty nationally. The first case of coronavirus disease 2019 (COVID‐19) in Arkansas occurred on 11 March 2020. Since then, approximately 8% of all Arkansans have tested positive. Given the resource limitations of Arkansas, COVID‐19 convalescent plasma (CCP) was explored as a potentially lifesaving, therapeutic option. Therefore, the Arkansas Initiative for Convalescent Plasma was developed to ensure that every Arkansan has access to this therapy. Study Design and Method: This brief report describes the statewide collaborative response from hospitals, blood collectors, and the Arkansas Department of Health (ADH) to ensure that CCP was available in a resource‐limited state. Results: Early contact tracing by ADH identified individuals who had come into contact with "patient zero" in early March. Within the first week, 32 patients tested positive for COVID‐19. The first set of CCP collections occurred on 9 April 2020. Donors had to be triaged carefully in the initial period, as many had recently resolved their symptoms. From our first collections, with appropriate resource and inventory management, we collected sufficient CCP to provide the requested number of units for every patient treated with CCP in Arkansas. Conclusions: The Arkansas Initiative, a statewide effort to ensure CCP for every patient in a resource‐limited state, required careful coordination among key players. Collaboration and resource management was crucial to meet the demand of CCP products and potentially save lives.